THE IDEOLOGICAL-AESTHETIC FOUNDATIONS OF STEPAN SEMCHUK'S CREATIVE WORK - Vivcharyk, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article analyzes the creative legacy of Stepan Semchuk as a poet, prose writer, playwright, critic, and a member of the literary group "Logos." The study is based on artistic works and literary-critical publications by Stepan Semchuk, printed both in Ukraine and abroad during the diaspora period of his activity. Similarities in artistic and stylistic principles, as well as shared views with other members of "Logos," are highlighted. It is illustrated that Stepan Semchuk's diverse body of work is marked by Christian morality, ethics, and national pathos at both thematic and formal levels. Genre definitions in the writer's works frequently include the genre of prayer, and the dramatic poem is closely associated with the mysterious genre. Biblical plots and images, especially Jesus Christ, the Mother of God, and prophets, are widespread in both the poetical and prose works of the writer, often serving as symbols or allegories. Attempts to genre-wise rejuvenate Ukrainian literature include epic poems, biblical narratives with lyrical elements. The biblical theme in Stepan Semchuk's works often projects onto Ukrainian historical events. Categories of religiosity and patriotism dominate the diverse body of work by Stepan Semchuk across different periods of his creative activity.